Apraxia of eyelid opening might be critical for levodopa-carbidopa intestinal gel treatment. (2020) - Kataoka, Hiroshi; Sawada, Yasuhiko; Shimozato, Naotaka; Inatomi, Shinichiro; Iguchi, Naohiko; Yoshiji, Hitoshi; Sugie, Kazuma
Abstract: Apraxia of eyelid opening (AEO) has been associated with levodopa. It has also been linked to impaired function of the frontal lobe, with the dopaminergic neuron projected to the frontal lobe. However, dopaminergic treatment for AEO is still controversial. Here we describe two patients with both Parkinson's disease (PD) and AEO, who responded differently to a continuous intrajejunal levodopa-carbidopa intestinal gel (LCIG) infusion. One of the patients manifested a deterioration of AEO after LCIG infusion, and off-periods were shortened by the decrease in the severity of dyskinesia. After discontinuing the use of LCIG, there was an improvement in the patient's ability to open her eyelids. The other patient had AEO prior to LCIG treatment, and this treatment spontaneously elevated her eyelids. These two PD patients raised the concern as to whether AEO may be a critical symptom for the indication of LCIG treatment. The different responses to LCIG might have been due to the fluctuation in brain dopamine levels during LCIG treatment. Highlights: We describe two patients with apraxia of lid opening (ALO). These patients with Parkinson's disease received treatment with LCIG. ALO differently responded to levodopa-carbidopa intestinal gel (LCIG). ALO might be critical for levodopa-carbidopa intestinal gel treatment.